Two decades of little change: An analysis of U.S. medical school basic science faculty by sex, race/ethnicity, and academic rank. - Christopher L Bennett; Raquel Y Salinas; Joseph J Locascio; Edward W Boyer (PLoS ONE, 2020)
To examine changes in U.S. medical school basic science faculty over the last 20 years (1998-2018), we undertook an observational study utilizing data from the American Association of Medical Colleges Faculty Roster. Rank (Instructor, Assistant Professor, Associate Professor, and Professor), sex (Female), and race/ethnicity (Asian, Black or African American, Hispanic, Latino, Spanish Origin, or Multiple Race-Hispanic, and White) were analyzed; this reflected a population of 14,047 (1998) to 18,601 (2018) faculty. Summary percent of faculty in various gender, race/ethnicity origin categories were analyzed across years of the study using regression models. We found that females (24.47% to 35.32%) were underrepresented at all timepoints and a minority of faculty identified as Black or African American (1.57% to 1.99%), Hispanic, Latino, Spanish Origin, or Multiple Race-Hispanic (3.03% to 4.44%), or Asian (10.90% to 20.41%). The largest population at all time points was White Male Professors (30.53% to 20.85%), followed by White Male Associate Professors (15.67% to 9.34%), and White Male Assistant Professors (13.22% to 9.75%). Small statistically significant increases were observed among female faculty and faculty at multiple ranks who identified as Black or African American or Hispanic, Latino, Spanish Origin, or Multiple Race-Hispanic. We then completed secondary analyses looking at the interaction of race/ethnicity and Gender. We found: (1) a significant increase (p<0.0001) in both genders who identify as Asian although males had a higher rate of increase (6 point difference, p<0.0001); (2) a significant increase for Black or African American females (P<0.01) not found among males; (3) significant increases (p<0.0001) among both genders of faculty who identify as Hispanic, Latino, Spanish Origin, or Multiple Race-Hispanic although females had an approximately 1% higher rate of increase; and (4) among faculty who identify as White, males had a significant decrease (p<0.0001) while females demonstrated an increase (p<0.0001).